Factors influencing the family planning method usage among married males in Turkey [Türkiye'de evli erkeklerin aile planlamasi yöntemlerini kullanmalarini etkileyen faktörler] - (:unkn) unknown (Gulhane Medical School, University of Health Sciences, 2006)
In this study, we aimed to determine the influencing factors on family planning methods usage of married males enrolled in the Turkish Population and Health Survey, which was conducted in 1998. Eight thousand and fifty nine (94%) out of 8596 houses selected for exampling were accessed. There were 3043 married men appropriate for interviewing, and 1971 (64.8%) of these responded the questionnaire. The ratio of using a modern method among family planning methods was 67.6%. These ratios were 58.5% and 61.5% for "urban" and "rural" regions, respectively. Using any method by males decreased by the increase in the duration of marriage, and increased by the age, educational status, number of child(ren), having social insurance (Social Insurance Organization, Retirement fund, and Baǧ-Kur), and hearing any information about AIDS. Using any modern method by males also decreased by the increase in the duration of marriage, and increased by the number of child(ren), living in the south part of the country, having social insurance, and hearing any information about AIDS. The ratio of condom using decreased by the duration of marriage and increased by the educational status. The use of withdrawal method increased by living in the western, southern and eastern parts of the country; and decreased by hearing any information about AIDS and by talking with friends about family planning. Results of the present study demonstrates the insufficiency of male involvement in family planning usage. "Consultation services on family planning" presented by Ministry of Health is highly recommended to become widespread. Equalizing the women's role with men in terms of gender issues is one of the additional basic solutions. © Gülhane Askeri Tip Akademisi 2006.
Keywords: Family planning services; Male participation; Turkey